Lightweight mortar incorporating various percentages of waste materials - Mehmannavaz, T.; Ismail, Mohamed; Sumadi, S.; Samadi, M.; Sajjadi, S. (Penerbit Universiti Teknologi Malaysia, 2014)
The experimental study evaluated the performance of lightweight aerated concrete incorporating various percentages of palm oil fuel ash (POFA) and pulverized fuel ash (PFA) as partial cement replacement. Performance evaluation of the aerated concrete was investigated with respect to ultimate compressive strength, density and strength development. Twelve mixes are developed and tested at different periods, i.e. 3, 7and 28 days. In this work, two different curing regime namely air curing and water curing were used to monitor the effect of the curing regime. The results show that the mixtures produced by replacing cement with POFA and PFA were comparable to the mix without cement replacement. Furthermore, this investigation observed that the cement-POFA-PFA based lightweight aerated concrete can be produced as lightweight non-load bearing concrete units, because hazard of ashes (POFA & PFA) might be a serious issue for human health. Disposal of ashes contributes the shortage of landfill space in all the worlds, especially in Malaysia.